MICROSTRUCTURE AND OXIDATION BEHAVIOR OF THE OXIDE DISPERSION STRENGTHENED STAINLESS STEEL 316L WITH ZIRCONIA DISPERSION - Ahda, Syahfandi; Agus Sujatno; Diene Hairani; Nanda Shabrina; Sulistioso Giat; Bandriyana (Majalah Ilmiah Pengkajian Industri, 2021)
Synthesis of the oxide dispersion sODS steels was performed by dispersing 0.5 wt % zirconia to the stainless steel SS 316L by the powder metallurgy method. The ball milling process was carried out for pre-alloying the elements continued with the consolidation performed by the compaction and sintering process using the APS (Arc Plasma Sintering). Analysis of microstructure was performed by observing the morphology, identify the phase and evaluate the oxide distribution. An oxidation test was carried out at 700oC for 8 hours using the MSB (Magnetic Suspension Balanced) apparatus to evaluate the primary oxidation curve. The same grain fineness consists of 2 dominant phases, so the presence of an austenitic phase and a ferritic phase has been analyzed from the X-Ray Diffraction pattern. The homogeneous distribution of zirconia was observed, followed by improvements in mechanical properties, which could be identified by hardness testing. The parabolic phenomenon oxidation curve was explained by the excellent high-temperature oxidation behaviour of the ODS steel, followed by the formation ofÂ  ZrO2 oxide protective thin layer.